2021
DOI: 10.1016/j.jhqr.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination among Spanish nephrologists: Acceptance and side effects

Abstract: Introduction. Four vaccines against Covid-19 have been approved to date. Their acceptance and safety have not been addressed on healthcare workers. The aim of the present study is to evaluate vaccination rates and side effects among Spanish nephrologists. Methods: All the Spanish nephrologists were invited to participate in this survey. Data on demographics, Covid-19 infection status, received vaccine doses and side effects were collected. Acceptance and side effects were analyzed for Covid-19 vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
1
9
0
5
Order By: Relevance
“… 56 In addition, seven studies reported combined results on more than one vaccine, collectively comprised of 9851 participants. Five of these studies were on BNT162b2 and mRNA‐1273, 72 , 73 , 74 , 75 , 76 one study with the addition of ChAdOx1 nCoV‐19 to the two previous vaccines, 77 and one study with BNT162b2 and ChAdOx1 nCoV‐19. 78 We categorized the studies base on the vaccines administered in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 In addition, seven studies reported combined results on more than one vaccine, collectively comprised of 9851 participants. Five of these studies were on BNT162b2 and mRNA‐1273, 72 , 73 , 74 , 75 , 76 one study with the addition of ChAdOx1 nCoV‐19 to the two previous vaccines, 77 and one study with BNT162b2 and ChAdOx1 nCoV‐19. 78 We categorized the studies base on the vaccines administered in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly reported comorbidities were hypertension, prior COVID-19, diabetes mellitus, cardiovascular disorders, autoimmune, rheumatologic or allergic disorders, malignancies, obesity, and anaphylaxis. 47,57,59,65,67,[70][71][72][73][74]78,118,[136][137][138][139] In addition, less common co-morbidities including asthma, thyroid disorder, psychological distress, hepatologic disease, and ophthalmologic disease were also mentioned in these studies.…”
Section: Precautions For Anaphylaxis 23mentioning
confidence: 99%
“…El número total de sospechas de RA con la 1ª dosis de las vacunas fue de 1.367, resultando la más prevalente el dolor en el punto de inyección, que afectó al 48 % de los vacunados y supuso un 75,8 % de las RA comunicadas, lo que coincide con otros estudios publicados (17,24,40,43), seguidas de cansancio, fatiga y escalofríos, sobre todo con VZ y JA, lo que ya aparecía en el 11º Informe de FV del Ministerio de Sanidad (44), dolor de cabeza y dolor muscular que aparecen a excepción de los escalofríos, en el mismo orden en el estudio de Amanzio et al (24). En los demás, aun coincidiendo en las RA más prevalentes, el orden difiere en todos ellos (34,(38)(39)(40)43).…”
Section: Sospechas De Reacciones Adversasunclassified
“…No se observaron diferencias significativas en relación con la condición de fumadores, vivir solo ni haberse contagiado de COVID-19 antes de la vacunación. En este último caso, este hecho sí se considera predictor de la aparición de síntomas tras la vacunación en otros estudios (34,40,43,45).…”
Section: Sospechas De Reacciones Adversasunclassified
“…Spanish nephrologists selfreported reasons for not being vaccinated include lack of appointment, pregnancy, contraindication, or previous COVID-19. 9 Finally, some questions were subjective, such as the appropriate personal protective equipment or the contagion source.…”
mentioning
confidence: 99%